S, Na and B co-doped cyano-rich graphite phase carbon nitride photoresponse catalyst as well as preparation method and application thereof

The S, Na, B co-doped cyanide-rich graphite phase carbon nitride photocatalyst addresses the efficiency limitations of gC3N4 by increasing surface area and carrier separation, achieving high rates of hydrogen and carbon dioxide production.

CN119140145AActive Publication Date: 2024-12-17SHAANXI HUATIM HYDROGEN ENERGY TECHNOLOGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411316823.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Current photocatalysts for hydrogen production, such as gC3N4, suffer from high carrier recombination rates and small specific surface areas, limiting their photocatalytic efficiency and industrial application potential.

Method used

A S, Na, B co-doped cyanide-rich graphite phase carbon nitride photocatalyst is synthesized through hydrothermal treatment and calcination using CH4N2S and NaBH4, enhancing the specific surface area and carrier separation efficiency.

Benefits of technology

The doped catalyst exhibits improved visible light photocatalytic hydrogen production rates up to 3637.9 μmol·h-1·g-1 and carbon dioxide reduction rates up to 779.2 μmol·h-1·g-1, with good stability and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140145A_ABST
    Figure CN119140145A_ABST
Patent Text Reader

Abstract

The invention discloses an S, Na and B co-doped cyano-rich graphite phase carbon nitride photoresponse catalyst and a preparation method and application thereof.The preparation method includes the steps that 10 g of urea with the purity being 99.9 wt%, 0.2-1 g of CH4N2S and 0.1-0.5 g of NaBH4 serve as raw materials of the catalyst, and a multi-element co-doped precursor material is prepared; then, the prepared multi-element co-doped precursor is calcined, and the S, Na and B co-doped cyano-rich g-C3N4 photocatalyst is prepared. Through the synergistic effect between cyano and (S, Na, B) atom doping, the light absorption range of g-C3N4 is widened, the specific surface area is increased, and the carrier recombination rate is reduced, so that the catalytic performance is improved; the specific surface area of the g-C3N4 photoresponse catalyst material obtained under the optimal optimization condition is 50.8 m < 2 >. G <-1 > and is 1.8 times that of the original g-C3N4; the catalytic hydrogen production activity within the wavelength range of 380-500 nm is 3637.9 [mu] mol.h <-1 >. G <-1 > which is 7.6 times that of the original g-C3N4, and the reduction rate of CO2 converted into CO is 779.2 [mu] mol.h <-1 >. G <-1 > which is 2.9 times that of the original g-C3N4; the method is easy to operate and good in repeatability, and the water decomposition hydrogen production efficiency and the CO2 reduction efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology and the advancement of global industrialization, the limited and rapid consumption of fossil energy has led to a serious energy crisis. At the same time, its development and utilization has also brought about serious environmental pollution problems, posing a huge threat to the survival and development of human society. Therefore, promoting the transformation of the global energy industry and society to a low-carbon economy and developing clean and efficient renewable energy have become ideal ways to promote the healthy and harmonious development of human society, and are also strategic goals in the field of energy technology in my country. Hydrogen energy has always been regarded as an ideal clean and renewable energy source with the characteristics of high energy density, excellent combustion performance, easy storage and transportation, and no pollution. Using solar energy to photocatalytically decompose water to produce hydrogen is a clean energy technology that converts solar energy into hydrogen energy, which is expected to achieve a sustainable "hydrogen economy". Among them, the preparation of non-toxic, cheap, efficient and stable visible light photocatalysts is one of the keys to this technology.

[0003] The reaction principle of photocatalytic hydrogen production includes three main steps: the first is the generation of photogenerated carriers. When light irradiates the surface of the photocatalyst, the valence band electrons absorb photons with energy greater than the band gap energy and transition to the conduction band to become photogenerated electrons, while the valence band forms photogenerated holes. These electron-hole pairs are called photogenerated carriers. Photogenerated electrons have the ability to reduce and participate in the hydrogen evolution reaction, and photogenerated holes have the ability to oxidize and participate in the oxygen evolution reaction. The second step is the transfer of photogenerated carriers. Some photogenerated carriers migrate to the surface and participate in the reaction. Only photogenerated carriers that successfully migrate and do not recombine can effectively participate in the reaction. The last step is the redox reaction. After some photogenerated carriers migrate to the surface, they combine with substances in the solution and participate in the redox reaction. In the photocatalytic decomposition of water to produce hydrogen, photogenerated electrons combine with hydrogen ions in water to generate hydrogen, and photogenerated holes oxidize the sacrificial agent into organic matter. In the actual reaction, a series of intermediate products may be produced. To ensure the photocatalytic decomposition of water to produce hydrogen, the energy band structure of the photocatalyst needs to meet certain requirements so that the photogenerated electrons participate in the hydrogen evolution reaction and the photogenerated holes participate in the oxygen evolution reaction. The photocatalyst needs to absorb energy, and the band gap energy corresponding to the shortest wavelength of sunlight is 4.2eV. According to the energy band structure of the photocatalyst, the band gap energy of the currently common photocatalysts is in the range of 1.23 to 4.2eV.

[0004] Since the energy of sunlight is mainly concentrated in the visible light region, the preparation of photocatalyst materials with visible light response has always been a hot topic and focus of research. 3 N 4) The photocatalyst has a band gap width of about 2.7eV, has good acid, alkali, light and thermal stability, is easy to control the morphology and energy band, can decompose water to produce hydrogen under visible light, and has been widely used in the field of photocatalysis. 3 N 4 The raw materials for the preparation of gC are abundant, the preparation method is simple, and the preparation cost is low, which has great application prospects and research value. 3 N 4 The efficiency of decomposing water to produce hydrogen cannot yet meet the requirements of industrial production, and it often exhibits low photocatalytic hydrogen production efficiency due to problems such as high carrier recombination rate and small specific surface area, limiting its potential application value. Summary of the invention

[0005] In order to overcome the defects of the prior art, the present invention aims to provide a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst and its preparation method and application. 3 N 4 With CH 4 N 2 S and NaBH 4 S, Na, and B co-doped cyanide-rich gC were prepared by hydrothermal treatment and calcination. 3 N 4 A reliable preparation scheme was developed, and photocatalytic water decomposition to produce hydrogen and CO 2 The reduction of CO is beneficial to the photocatalytic decomposition of water to produce hydrogen and 2 The industrial application of reduction has the characteristics of simple operation, good repeatability, cheap and easy to obtain raw materials, and the prepared product has excellent visible light catalytic performance of decomposing water to produce hydrogen.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the raw materials of which include: 10g urea, 0.2-1g CH 4 N 2 S and 0.1-0.5 g NaBH 4 All three were of analytical grade 99.9wt%.

[0008] A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific steps comprising:

[0009] Step 1: 10g urea with a purity of 99.9wt%, 0.2-1g CH 4 N 2 S and 0.1-0.5 g NaBH 4, preparing a multi-element co-doped precursor material; preparing a multi-element co-doped precursor material;

[0010] Step 2: calcining the multi-element co-doped precursor obtained in step 1 to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0011] The specific method of step 1 is: weigh 10g of 99.9wt% urea, and heat it in air at 2-5℃·min -1 The mixture was calcined at 500-550°C for 2-4h at a heating rate of 1.5-2.0 °C. The obtained mixture was ground into powder and named CN. 0.5 g CN, 0.2-1 g CH 4 N 2 S and 99.9wt% 0.1-0.5g NaBH 4 Add 30-50 mL H 2 O to obtain a solution, and heat the solution from room temperature to 100-120°C oil bath under magnetic stirring and maintain for 2-4 hours; gradually evaporate the solution to dryness to obtain a slurry, and add 30-50mL 1:1 ethanol / H 2 O solution is added to the slurry and stirred for 30-60 min; the slurry is vacuumed for 5-15 min to obtain a solid compound, which is dried in air at 60-85 ° C for 3-5 h to obtain multi-element co-doped gC 3 N 4 Precursor materials.

[0012] The specific method of step 2 is: weigh 0.5-1g of the material precursor, calcine it at 500-550°C for 4-6h in an Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0013] A method for photocatalytically decomposing water to produce hydrogen using S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific method being:

[0014] Add 20.0-50 mg of the prepared S, Na, B co-doped cyanide-rich gC into the reactor 3 N 4 The photocatalyst is a photocatalyst, wherein 80 mL of a triethanolamine aqueous solution having a triethanolamine content of 8-16 mL is added as a sacrificial agent; and 0.571-1.43 mL of a hexahydrate chloroplatinic acid aqueous solution having a concentration of 0.0007 g / mL is added as a co-catalyst, and metal platinum is photodeposited onto the S, Na, and B co-doped cyanide-rich gC under a xenon lamp. 3 N 4 on the catalyst;

[0015] Argon gas was purged into the reactor for 10-20 minutes to remove oxygen and eliminate the interference of oxygen in the reactor. The reactor was maintained at a fixed temperature of 30-40°C by circulating water. The magnetic stirrer was turned on and the xenon lamp was turned on for illumination. The hydrogen was quantitatively detected by gas chromatography.

[0016] A method for reducing carbon dioxide using S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific method being:

[0017] Add 10.0-20.0 mg of the prepared S, Na, and B co-doped cyanide-rich gC into the reactor. 3 N 4 Photocatalyst, add 4-8mL deionized water, 1-2mL triethanolamine and 10-20mL acetonitrile, stir with a magnetic stirrer to obtain a uniform dispersion, then add 8-16mg [Ru(bpy)) 3 ]Cl 2 6H 2 O was added to the dispersion as a photosensitizer;

[0018] Use CO 2 The reactor was purged for 30-40 minutes to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at a fixed temperature in the range of 30-40°C. The magnetic stirrer was turned on and the xenon lamp was turned on for illumination. The CO of the photocatalytic product was analyzed by gas chromatography. 2 The reduction rate to CO was quantitatively detected.

[0019] Compared with the prior art, the beneficial effects of the present invention are:

[0020] This invention uses CH for the first time 4 N 2 S and NaBH 4 The S, Na, and B co-doped cyanide-rich gC was synthesized by the common hydrothermal modification process. 3 N 4 This S, Na, and B co-doped cyanide-rich gC 3 N 4 It has a large specific surface area and good light absorption performance, which effectively promotes gC under visible light irradiation 3 N 4 The separation and migration of internal photogenerated carriers show good visible light photocatalytic hydrogen production activity and carbon dioxide reduction performance, and the visible light photocatalytic hydrogen production rate reaches 3637.9 μmol·h -1 ·g -1 , and has good hydrogen production stability, CO 2 The reduction rate to CO reached 779.2 μmol·h -1 ·g-1 ; The visible light photocatalytic hydrogen production rate and CO reduction rate were greatly improved.

[0021] The present invention directly obtains gC by calcining urea in air. 3 N 4 With CH 4 N 2 S and NaBH 4 The S, Na, B co-doped precursor was hydrothermally treated together to form the S, Na, B co-doped cyanide-rich gC 3 N 4 Photoresponsive catalyst materials; Synergistic effect between cyanide and (S, Na, B) atom doping makes gC 3 N 4 The light absorption range is broadened; CH4N2S and NaBH4 are used to modify the prepared g-C3N4, and a new g-C3N4 visible light responsive catalyst material is constructed, which has excellent properties such as large specific surface area, low crystallinity, narrow band gap, and suitable carrier lifetime to improve the photocatalytic efficiency.

[0022] In summary, the present invention is simple to operate, has good repeatability, and uses cheap and easily available raw materials. The prepared product has excellent visible light catalytic water decomposition and hydrogen production performance, and provides a reliable solution for the development and application of new photocatalysts for improving the efficiency of photocatalytic water decomposition and hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is S, Na, B co-doped cyanide-rich gC 3 N 4 X-ray diffraction (XRD) pattern.

[0024] Figure 2 It is S, Na, B co-doped cyanide-rich gC 3 N 4 Fourier transform infrared (FTIR) spectrum.

[0025] Figure 3 is a cyanide-rich gC co-doped with S, Na, and B. 3 N 4 X-ray photoelectron spectroscopy (XPS) diagram: Figure 3 (a) is in CNS-NaB 0.5 Figure 3(b) is the peak of S2p detected in the sample; Figure 3(c) is the peak of Na 1s; Figure 3(c) is the peak of B1s.

[0026] Figure 4 It is CN and S, Na, B co-doped cyanide-rich gC 3 N 4 UV-visible absorption spectrum.

[0027] Figure 5(a) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 N 2 Adsorption–desorption isotherms.

[0028] Figure 5(b) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 BJH pore size distribution diagram.

[0029] Figure 6(a) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 Steady-state PL spectrum of .

[0030] Figure 6(b) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 Transient PL spectrum of .

[0031] Figure 7 It is S, Na, B co-doped cyanide-rich gC 3 N 4 X-ray diffraction (SEM) pattern.

[0032] Figure 8 It is S, Na, B co-doped cyanide-rich gC 3 N 4 Transmission electron microscope (TEM) photograph.

[0033] Figure 9(a) shows S, Na, and B co-doped cyanide-rich gC 3 N 4 Visible light photocatalytic hydrogen production rate diagram.

[0034] Figure 9(b) shows S, Na, and B co-doped cyanide-rich gC 3 N 4 Visible light photocatalytic hydrogen production stability test diagram.

[0035] Figure 10(a) is a S, Na, B co-doped cyanide-rich gC 3 N 4 Visible light photocatalytic reduction of carbon dioxide rate diagram.

[0036] Figure 10(b) shows S, Na, and B co-doped cyanide-rich gC 3 N 4 Visible light photocatalytic reduction of carbon dioxide stability test diagram. DETAILED DESCRIPTION

[0037] Embodiment 1:

[0038] A S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the raw materials of which include: 10g urea, 0.5g CH 4 N 2 S and 0.5 g NaBH 4 All three were of analytical grade 99.9wt%.

[0039] A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific steps are as follows:

[0040] Step 1: Weigh 10 g of 99.9 wt% urea, add it to a ceramic crucible with a lid, and incubate in air at 5 °C min -1 The mixture was calcined at 550 °C for 4 h at a heating rate of 1.5 % and ground into powder, which was named CN. 0.5 g CN, 99.9 wt% CH 4 N 2 S and 99.9wt% 0.5g NaBH 4 Add 30mL H 2 O to obtain a solution, which was heated from room temperature to a 120°C oil bath under magnetic stirring and maintained for 2 h; the solution was gradually evaporated to dryness to obtain a slurry, and 30 mL of 1:1 ethanol / H 2 O solution was added to the slurry and stirred for 30 min; the solid compound was obtained by vacuuming the slurry for 10 min, and dried in air at 80 ° C for 3 h to obtain multi-element co-doped gC 3 N 4 Precursor materials;

[0041] Step 2: Weigh 1g of multi-element co-doped gC 3 N 4 The precursor material was spread in a square (6 cm x 3 cm x 2 cm) and calcined at 500 °C for 4 h in an Ar atmosphere in a tube furnace to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0042] An application method of photocatalytic water decomposition and hydrogen production by S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, specifically comprising:

[0043] In a glass side window reactor with a volume of 105 mL, 20.0 mg of S, Na, and B co-doped cyanide-rich gC obtained in step 2 was added. 3 N 4Photocatalyst, add 80mL of triethanolamine aqueous solution with a triethanolamine content of 10mL; and add 0.571mL of hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007g / mL as a co-catalyst, and deposit metal platinum on S, Na, B co-doped cyanide-rich gC under a xenon lamp. 3 N 4 on the catalyst;

[0044] Argon was purged through the glass side window reactor for 15 minutes to remove oxygen and eliminate the interference of oxygen in the air in the reactor. The reactor was maintained at 35°C by circulating water, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination; hydrogen was quantitatively detected by gas chromatography.

[0045] An application method of S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst for carbon dioxide reduction, specifically:

[0046] In a glass side window reactor with a volume of 105 mL, 10.0 mg of S, Na, and B co-doped cyanide-rich gC prepared in step 2 was added. 3 N 4 Photocatalyst, add 4 mL of deionized water, 1 mL of triethanolamine and 10 mL of acetonitrile, stir with a magnetic bar to obtain a uniform dispersion, then add 8 mg [Ru(bpy)) 3 ]Cl 2 6H 2 O was added to the dispersion as a photosensitizer;

[0047] Use CO 2 The reaction was purged for 30 min to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at 35 °C, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination. The CO of the photocatalytic product was analyzed by gas chromatography. 2 The reduction rate to CO was quantitatively detected.

[0048] Embodiment 2:

[0049] A S, Na, B co-doped cyanide-rich graphite phase carbon nitride light-responsive catalyst, characterized in that its raw materials include: 10g urea, 1g CH 4 N 2 S and 0.5 g NaBH 4 All three were of analytical grade 99.9wt%.

[0050] A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific steps are as follows:

[0051] Step 1: Weigh 10 g of 99.9 wt% urea into a ceramic crucible with a lid and incubate in air at 4 °C min -1The heating rate was calcined at 550℃ for 3h, and the yellow powder gC 3 N 4 Grind into powder and name it CN; weigh 0.5g CN, 99.9wt% 1g CH 4 N 2 S and 99.9wt% 0.5g NaBH 4 Add 30 mL of H 2 O to obtain a solution, which was heated from room temperature to a 100°C oil bath under magnetic stirring and maintained for 4 h; the solution was gradually evaporated to dryness to obtain a slurry, and 40 mL of 1:1 ethanol / H 2 O solution was added to the slurry and stirred for 40 min; the solid compound was obtained by vacuuming the slurry for 5 min, and dried in air at 70 ° C for 3 h to obtain multi-element co-doped gC 3 N 4 Precursor materials;

[0052] Step 2: Weigh 1g of multi-element co-doped gC 3 N 4 The precursor material was spread in a square (6 cm x 3 cm x 2 cm) and calcined at 550 °C for 3 h in a tube furnace under Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0053] An application method of photocatalytic water decomposition and hydrogen production by S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, specifically comprising:

[0054] In a glass side window reactor with a volume of 105 mL, 20.0 mg of S, Na, and B co-doped cyanide-rich gC obtained in step 2 was added. 3 N 4 Photocatalyst, add 80mL of triethanolamine aqueous solution with a triethanolamine content of 10mL; and add 0.571mL of hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007g / mL as a co-catalyst, and deposit metal platinum on S, Na, B co-doped cyanide-rich gC under a xenon lamp. 3 N 4 on the catalyst;

[0055] Argon was purged through the glass side window reactor for 10 minutes to remove oxygen and eliminate the interference of oxygen in the air in the reactor. The reactor was maintained at 36°C by circulating water, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination; hydrogen was quantitatively detected by gas chromatography.

[0056] An application method of S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst for carbon dioxide reduction, specifically:

[0057] In a glass side window reactor with a volume of 105 mL, 10.0 mg of S, Na, and B co-doped cyanide-rich gC prepared in step 2 was added. 3 N 4 Photocatalyst, add 4 mL of deionized water, 1 mL of triethanolamine and 10 mL of acetonitrile, stir with a magnetic stirrer to obtain a uniform dispersion, then add 10 mg [Ru(bpy) 3 ]Cl 2 6H 2 O was added to the dispersion as a photosensitizer;

[0058] Use CO 2 The reaction was purged for 40 min to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at 36 °C, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination. The CO of the photocatalytic product was analyzed by gas chromatography. 2 The reduction rate to CO was quantitatively detected.

[0059] Embodiment 3:

[0060] A S, Na, B co-doped cyanide-rich graphite phase carbon nitride light-responsive catalyst, characterized in that its raw materials include: 10g urea, 1g CH 4 N 2 S and 0.3 g NaBH 4 All three were of analytical grade 99.9wt%.

[0061] A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific steps are as follows:

[0062] Step 1: Weigh 10 g of 99.9 wt% urea into a ceramic crucible with a lid and incubate in air at 5 °C min -1 The heating rate was calcined at 530℃ for 3h, and the yellow powder gC 3 N 4 Grind and name it CN; weigh 0.5g CN, 1g CH 4 N 2 S and 99.9wt% 0.3g NaBH 4 Add 30mL H 2 O to obtain a solution, which was heated from room temperature to 110 °C oil bath under magnetic stirring and maintained for 3 h; the solution was gradually evaporated to dryness to obtain a slurry, and 36 mL of 1:1 ethanol / H 2 O solution was added to the slurry and stirred for 30 min. The slurry was vacuumed for 10 min to obtain a solid compound, which was dried in air at 80 °C for 3 h to obtain a multi-element co-doped precursor material;

[0063] Step 2: Weigh 1 g of the precursor and spread it in a square (6 cm x 3 cm x 2 cm), and calcine it at 530 ° C for 3 h in a tube furnace under Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0064] An application method of photocatalytic water decomposition and hydrogen production by S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, specifically comprising:

[0065] In a glass side window reactor with a volume of 105 mL, 20.0 mg of S, Na, and B co-doped cyanide-rich gC obtained in step 2 was added. 3 N 4 Photocatalyst, add 80mL of triethanolamine aqueous solution with a triethanolamine content of 10mL; and add 0.571mL of hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007g / mL as a co-catalyst, and deposit metal platinum on S, Na, B co-doped cyanide-rich gC under a xenon lamp. 3 N 4 on the catalyst;

[0066] Before illumination, argon was purged through the reactor for 10 minutes to remove oxygen in the system (eliminating the interference of oxygen in the air in the reactor), the reactor was maintained at 34°C by circulating water, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination; hydrogen was quantitatively detected by gas chromatography.

[0067] An application method of S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst for carbon dioxide reduction, specifically:

[0068] In a glass side window reactor with a volume of 105 mL, 10.0 mg of S, Na, and B co-doped cyanide-rich gC prepared in step 2 was added. 3 N 4 Photocatalyst, add 4 mL of deionized water, 1 mL of triethanolamine and 10 mL of acetonitrile, and 8 mg [Ru(bpy) 3 ]Cl 2 6H 2 O was added to the dispersion as a photosensitizer;

[0069] Use CO 2 The reaction was purged for 35 min to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at 34 °C, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination. The CO of the photocatalytic product was analyzed by gas chromatography. 2 The reduction rate to CO was quantitatively detected.

[0070] Embodiment 4:

[0071] A S, Na, B co-doped cyanide-rich graphite phase carbon nitride light-responsive catalyst, characterized in that its raw materials include: 10g urea, 0.6g CH 4 N 2 S and 0.5 g NaBH 4 All three were of analytical grade 99.9wt%.

[0072] A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific steps are as follows:

[0073] Step 1: Weigh 10 g of 99.9 wt% urea into a ceramic crucible with a lid and incubate in air at 5 °C min -1 The heating rate was calcined at 500℃ for 4h, and the yellow powder gC 3 N 4 Grind and name it CN; weigh 0.5g CN, 0.6g CH 4 N 2 S and 99.9wt% 0.5g NaBH 4 Add 30 mL of H 2 O to obtain a solution, which was heated from room temperature to a 120°C oil bath under magnetic stirring and maintained for 4 h; the solution was gradually evaporated to dryness to obtain a slurry, and 40 mL of 1:1 ethanol / H 2 O solution was added to the slurry and stirred for 60 min; the slurry was vacuumed for 15 min to obtain a solid compound, which was dried in air at 60 °C for 5 h to obtain a multi-element co-doped precursor material;

[0074] Step 2: Weigh 1 g of the precursor and spread it in a square (6 cm x 3 cm x 2 cm), and calcine it at 500 °C for 4 h in a tube furnace under Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0075] An application method of photocatalytic water decomposition and hydrogen production by S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, specifically comprising:

[0076] In a glass side window reactor with a volume of 105 mL, 20.0 mg of S, Na, and B co-doped cyanide-rich gC obtained in step 2 was added. 3 N 4 Photocatalyst, add 80mL of triethanolamine aqueous solution with a triethanolamine content of 10mL; and add 1.43mL of hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007g / mL as a co-catalyst, and deposit metal platinum on S, Na, B co-doped cyanide-rich gC under a xenon lamp. 3N 4 on the catalyst;

[0077] Before illumination, argon was purged through the reactor for 10 minutes to remove oxygen in the system (eliminating the interference of oxygen in the air in the reactor), the reactor was maintained at 35°C by circulating water, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination; hydrogen was quantitatively detected by gas chromatography.

[0078] An application method of S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst for carbon dioxide reduction, specifically:

[0079] In a glass side window reactor with a volume of 105 mL, 10.0 mg of S, Na, and B co-doped cyanide-rich gC prepared in step 2 was added. 3 N 4 Photocatalyst, add 4 mL of deionized water, 1 mL of triethanolamine and 10 mL of acetonitrile, and 8 mg [Ru(bpy) 3 ]Cl 2 6H 2 O was added to the dispersion as a photosensitizer;

[0080] Use CO 2 The reaction was purged for 40 min to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at 35 °C, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination. The CO of the photocatalytic product was analyzed by gas chromatography. 2 The reduction rate to CO was quantitatively detected.

[0081] Embodiment 5:

[0082] A S, Na, B co-doped cyanide-rich graphite phase carbon nitride light-responsive catalyst, characterized in that its raw materials include: 10g urea, 0.8g CH 4 N 2 S and 0.3 g NaBH 4 All three were of analytical grade 99.9wt%.

[0083] A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, the specific steps are as follows:

[0084] Step 1: Weigh 10 g of 99.9 wt% urea into a ceramic crucible with a lid and incubate in air at 5 °C min -1 The heating rate was calcined at 550℃ for 4h, and the yellow powder gC 3 N 4 Grind and name it CN. Weigh 0.5g CN, 0.8g CH 4 N 2S and 99.9wt% 0.3g NaBH 4 Add 30 mL of H 2 O to obtain a solution, which was heated from room temperature to a 120°C oil bath under magnetic stirring and maintained for 2 h; the solution was gradually evaporated to dryness to obtain a slurry, and 40 mL of 1:1 ethanol / H 2 O solution was added to the slurry and stirred for 30 min; the slurry was vacuumed for 10 min to obtain a solid compound, which was dried in air at 80 °C for 3 h to obtain a multi-element co-doped precursor material;

[0085] Step 2: Weigh 1g of the precursor and spread it in a square (6cm x 3cm x 2cm), and calcine it at 550℃ for 4h in a tube furnace under Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich gC 3 N 4 Photocatalyst.

[0086] An application method of photocatalytic water decomposition and hydrogen production by S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, specifically comprising:

[0087] In a glass side window reactor with a volume of 105 mL, 20.0 mg of S, Na, and B co-doped cyanide-rich gC obtained in step 2 was added. 3 N 4 Photocatalyst, add 80mL of triethanolamine aqueous solution with a triethanolamine content of 10mL; and add 0.571mL of hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007g / mL as a co-catalyst, and deposit metal platinum on S, Na, B co-doped cyanide-rich gC under a xenon lamp. 3 N 4 on the catalyst;

[0088] Before illumination, argon was purged through the reactor for 20 minutes to remove oxygen in the system (eliminating the interference of oxygen in the air in the reactor), the reactor was maintained at 36°C by circulating water, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination; hydrogen was quantitatively detected by gas chromatography.

[0089] An application method of S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst for carbon dioxide reduction, specifically:

[0090] In a glass side window reactor with a volume of 105 mL, 10.0 mg of S, Na, and B co-doped cyanide-rich gC prepared in step 2 was added. 3 N 4 Photocatalyst, add 4 mL of deionized water, 1 mL of triethanolamine and 10 mL of acetonitrile, and 8 mg [Ru(bpy) 3 ]Cl 2 6H2 O was added to the dispersion as a photosensitizer;

[0091] Use CO 2 The reaction was purged for 40 min to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at 36 °C, the magnetic stirrer was turned on, and the xenon lamp was turned on for illumination. The CO of the photocatalytic product was analyzed by gas chromatography. 2 The reduction rate to CO was quantitatively detected.

[0092] Figure 1 It is S, Na, B co-doped cyanide-rich gC 3 N 4 X-ray diffraction (XRD) patterns of all samples show that they have graphite carbon nitride (gC 3 N 4 ), except for the CNS sample, the peak intensities of the modified samples at 12.8° and 27.2° are lower, indicating that the Na / B atoms are successfully incorporated into the CN structure, destroying the long-range ordered structure of the heptazine ring unit structure inside the carbon nitride, enhancing the disorder of the carbon nitride structure and increasing the interlayer spacing, which is beneficial to promoting the improvement of the specific surface area.

[0093] Figure 2 It is S, Na, B co-doped cyanide-rich gC 3 N 4 FTIR spectrum of NaBH 4 After the introduction of CN, at 2178cm -1 A new peak appears at , which can be attributed to the asymmetric stretching vibration of cyano (-C≡N), that is, the generation of a cyano-rich structure. As an electron-withdrawing group, cyano can promote the separation and migration efficiency of photogenerated electrons in carbon nitride and improve the utilization rate of photogenerated electrons.

[0094] Figure 3 is a cyanide-rich gC co-doped with S, Na, and B. 3 N 4 X-ray photoelectron spectroscopy (XPS) of CNS-NaB 0.5 The S2p peak was detected in the sample; Figure 3(b) is the Na 1s peak; Figure 3(c) is the B1s peak; the atomic ratio is S (0.10%), Na (1.16%) and B (0.07%), confirming the successful co-doping of (S, Na, B).

[0095] Figure 4 It is CN and S, Na, B co-doped cyanide-rich gC 3 N 4 UV-visible absorption spectrum, the original CN has a light absorption edge at 460nm, and the co-doped CNS-NaB 0.5The samples show a red shift and an expanded light absorption range of up to 500 nm, indicating that the co-doping of S, Na, and B changes the electronic structure of CN, reduces the band gap, and increases the visible light absorption response.

[0096] Figure 5(a) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 N 2 Adsorption-desorption isotherms. Both samples showed type IV isotherms and had significant H3 hysteresis loops, indicating that the samples were composed of mesoporous structures. 0.5 The BET surface areas of the samples are 27.2 and 50.8 m 2 ·g -1 , indicating that the co-doping of S, Na, and B significantly increased the specific surface area of ​​CN.

[0097] Figure 5(b) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 BJH pore size distribution of CNS-NaB 0.5 The pore volume of the sample is 0.23 cm 3 ·g -1 , pore size is 20.22nm, CNS-NaB 0.5 Compared with CN, it has more porous structures.

[0098] Figure 6(a) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 Steady-state PL spectra of CNS-NaB 0.5 The PL intensity of the sample is weaker than that of CN, indicating that CNS-NaB 0.5 The photoinduced charge carrier separation in the sample is enhanced, that is, the co-doping of S, Na, and B suppresses the recombination of the ground state, and the cyanide group can accelerate and improve the charge transfer mechanism in the photocatalytic reaction.

[0099] Figure 6(b) shows the cyanide-rich gC co-doped with CN, S, Na, and B. 3 N 4 Transient PL spectra of CNS-NaB 0.5 The average lifetime of the sample (1.58 ns) is shorter than that of pristine CN (5.07 ns), indicating that CNS-NaB 0.5 The electron-hole separation and transfer in the sample are rapid.

[0100] Figure 7 It is S, Na, B co-doped cyanide-rich gC 3 N 4 Scanning electron microscope (SEM) photo. It can be clearly seen that gC 3 N 4Ultra-thin nanosheet structure, uniform size distribution, and obvious mesoporous channels. The increased specific surface area and rich pore structure increase the number of active sites, which is conducive to promoting the adsorption of reaction substrates and mass transfer.

[0101] Figure 8 It is S, Na, B co-doped cyanide-rich gC 3 N 4 The transmission electron microscope (TEM) photo of gC 3 N 4 Ultrathin nanosheet structure.

[0102] Figure 9(a) shows S, Na, and B co-doped cyanide-rich gC 3 N 4 Visible light photocatalytic hydrogen production activity diagram, when NaBH 4 The visible light photocatalytic water decomposition hydrogen production rate of the catalyst prepared when the catalyst was 0.5g was the highest, reaching 3637.9μmol·h -1 ·g -1 .

[0103] Figure 9(b) shows S, Na, and B co-doped cyanide-rich gC 3 N 4 The visible light catalytic hydrogen production stability test chart shows that after 3 cycles of photocatalytic reaction for a total of 15 hours, the hydrogen production rate of the catalyst did not decrease significantly, indicating that the catalyst has good stability.

[0104] Figure 10(a) is a S, Na, B co-doped cyanide-rich gC 3 N 4 Visible light catalytic reduction of CO 2 Activity diagram, when NaBH 4 Visible light catalytic reduction of CO by the catalyst prepared when the catalyst was 0.5 g 2 The highest rate can reach 779.2 μmol·h -1 ·g -1 .

[0105] Figure 10(b) shows S, Na, and B co-doped cyanide-rich gC 3 N 4 Visible light catalytic reduction of CO 2 Stability test diagram, after three cycles of testing, CO 2 The reduction performance decreased within an acceptable range, indicating that the catalyst has good stability.

Claims

1. A S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, characterized in that: The raw materials include: 10g urea, 0.2-1g CH4N2S and 0.1-0.5g NaBH4, all of which are 99.9wt% analytically pure.

2. A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, characterized in that: The specific steps include: Step 1: Prepare a multi-element co-doped precursor material with 10g urea of ​​99.9wt% purity, 0.2-1g CH4N2S of 99.9wt% and 0.1-0.5g NaBH4 of 99.9wt% purity; Step 2: calcining the multi-element co-doped precursor obtained in step 1 to obtain S, Na, and B co-doped cyanide-rich g-C3N4 photocatalyst.

3. A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, characterized in that: The specific method of step 1 is: weigh 10g of 99.9wt% urea, and heat it in air at 2-5℃·min -1 The mixture was calcined at 500-550°C for 2-4h at a heating rate of 100-250 ℃, and the resultant was ground into powder and named CN; 0.5g CN, 0.2-1g CH4N2S of 99.9wt% and 0.1-0.5g NaBH4 of 99.9wt% were weighed and added into 30-50mL H2O in sequence to obtain a solution, and the solution was heated from room temperature to 100-120°C in an oil bath under magnetic stirring and maintained for 2-4h; the solution was gradually evaporated to dryness to obtain a slurry, and 30-50mL 1:1 ethanol / H2O solution was added to the slurry and stirred for 30-60min; a solid compound was obtained by evacuating the slurry for 5-15min, and the solid compound was dried in air at 60-85°C for 3-5h to obtain a multi-element co-doped g-C3N4 precursor material.

4. A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, characterized in that: The specific method of step 2 is: weigh 0.5-1g of material precursor, calcine at 500-550°C for 4-6h under Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich g-C3N4 photocatalyst.

5. A method for photocatalytically decomposing water to produce hydrogen using S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, characterized in that: The specific method is: 20.0-50 mg of the prepared S, Na, B co-doped cyanide-rich g-C3N4 photocatalyst is added to the reactor, and 80 mL of a triethanolamine aqueous solution with a triethanolamine content of 8-16 mL is added as a sacrificial agent; 0.571-1.43 mL of a hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007 g / mL is added as a co-catalyst, and metal platinum is optically deposited on the S, Na, B co-doped cyanide-rich g-C3N4 catalyst under a xenon lamp; Argon gas was purged into the reactor for 10-20 minutes to remove oxygen and eliminate the interference of oxygen in the reactor. The reactor was maintained at a fixed temperature of 30-40°C by circulating water. The magnetic stirrer was turned on and the xenon lamp was turned on for illumination. The hydrogen was quantitatively detected by gas chromatography.

6. A method for reducing carbon dioxide using S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst, characterized in that: The specific method is: 10.0-20.0 mg of the prepared S, Na, B co-doped cyanide-rich g-C3N4 photocatalyst is added to the reactor, 4-8 mL of deionized water, 1-2 mL of triethanolamine and 10-20 mL of acetonitrile are added, and a magnetic stirrer is added to obtain a uniform dispersion, and then 8-16 mg of [Ru(bpy))3]Cl2·6H2O is added to the dispersion as a photosensitizer; The reactor was purged with CO2 for 30-40 minutes to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at a fixed temperature within the range of 30-40°C. The magnetic stirrer was turned on and the xenon lamp was turned on for illumination. Gas chromatography was used for quantitative detection of the photocatalytic products.

7. The S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst according to claim 1, characterized in that: The raw materials include: 10g urea, 0.5g CH4N2S and 0.5g NaBH4, all of which are analytically pure with a purity of 99.9wt%.

8. A method for preparing a S, Na, B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst according to any one of claims 2 to 4, characterized in that: The specific steps are: Step 1: Weigh 10g of 99.9wt% urea and incubate at 5℃·min in air -1 The mixture was calcined at 550°C for 4 h at a heating rate of 100 wt %, and the resultant was ground into powder and named CN; 0.5 g CN, 0.5 g CH4N2S of 99.9 wt % and 0.5 g NaBH4 of 99.9 wt % were weighed and added to 30 mL H2O in sequence to obtain a solution, and the solution was heated from room temperature to 120°C in an oil bath under magnetic stirring and maintained for 2 h; the solution was gradually evaporated to dryness to obtain a slurry, and 30 mL of 1:1 ethanol / H2O solution was added to the slurry and stirred for 30 min; a solid compound was obtained by evacuating the slurry for 10 min, and dried in air at 80°C for 3 h to obtain a multi-element co-doped g-C3N4 precursor material; Step 2: Weigh 1 g of multi-element co-doped g-C3N4 precursor material and calcine it at 500°C for 4 h in an Ar atmosphere to obtain S, Na, and B co-doped cyanide-rich g-C3N4 photocatalyst.

9. The method for producing hydrogen by photocatalytically splitting water using S, Na, and B co-doped cyanide-rich graphite phase carbon nitride light-responsive catalyst according to claim 5, characterized in that: The specific method is: In a reactor with a volume of 105 mL, 20.0 mg of the S, Na, B co-doped cyanide-rich g-C3N4 photocatalyst obtained in step 2 was added, and 80 mL of a triethanolamine aqueous solution with a triethanolamine content of 10 mL was added; and 0.571 mL of a hexahydrate chloroplatinic acid aqueous solution with a concentration of 0.0007 g / mL was added as a co-catalyst, and metal platinum was photodeposited onto the S, Na, B co-doped cyanide-rich g-C3N4 catalyst under a xenon lamp; Argon was passed through the reactor for 15 minutes to remove oxygen and eliminate the interference of oxygen in the air in the reactor. The reactor was maintained at 35°C by circulating water, a magnetic stirrer was turned on, and a xenon lamp was turned on for illumination. Gas chromatography was used to quantitatively detect hydrogen.

10. The method for reducing carbon dioxide using S, Na, and B co-doped cyanide-rich graphite phase carbon nitride photoresponsive catalyst according to claim 6, characterized in that: The specific method is: In a reactor with a volume of 105 mL, 10.0 mg of the S, Na, B co-doped cyanide-rich g-C3N4 photocatalyst prepared in step 2 was added, 4 mL of deionized water, 1 mL of triethanolamine and 10 mL of acetonitrile were added, and a magnetic stirrer was added to obtain a uniform dispersion. Then, 8 mg of [Ru(bpy))3]Cl2·6H2O was added to the dispersion as a photosensitizer; The reaction was purged with CO2 for 30 minutes to remove air and reach adsorption-desorption equilibrium. The reaction temperature was controlled at 35°C, a magnetic stirrer was turned on, and a xenon lamp was turned on for illumination. Gas chromatography was used to quantitatively detect the reduction rate of CO2 in the photocatalytic product to CO.

Citation Information

Patent Citations

  • Synthesis method of nonmetal B and P doped graphite phase carbon nitride photocatalyst

    CN116550367A

  • Co-doped carbon nitride photocatalytic composite material as well as preparation method and application thereof

    CN117123252A

  • Phosphorus-doped tubular carbon nitride micro-nano material and application thereof in catalytic treatment of exhaust gas

    US20200282384A1